Eficácia do Enalapril na prevenção da cardiotoxicidade induzida pelo antimoniato de meglumina no tratamento da leishmaniose tegumentar americana. - Alex Miranda Rodrigues (2012)
Introduction: Cutaneous leishmaniasis (CL) is an infectious disease endemic all over Brazil. Antimony compounds are the cornerstone of treatment of CL. This group of drugs has high frequency of adverse effects; an important effect is cardiotoxicity, leading to severe arrhythmias and even death. Inhibitors of angiotensin converting enzyme have shown in observational studies an cardioprotective effect during treatment of CL with meglumine antimoniate.Objectives: : The main objective is to identify the effect of ACE inhibitors on prevention of QTc enlargement and ventricular repolarization abnormalities induced by meglumine antimoniate. To identify the effect of ACE inhibitors in levels of troponin T during treatment fo CL with meglumine antimony and the potential use of troponin T as marker of cardiotoxicity during treatment of CL with meglumine antimoniate. Identify adverse effects during treatment of CL with meglumine antimony and the influence of ACE inhibitors on adverse effects. Methods: : We conducted a randomized controlled trial, doubleblinding using enalapril and placebo. thirty patients with definite diagnosis of CL and indication of use of meglumine antimoniate were randomically allocated to receive enalapril or placebo. All patients were clinically, electrocardiographic and laboratorial evaluate before the treatment and in the 5th, 10th, 15th, 25th and 35th day after the beginning of treatment. ECG tracking were blinded read by a doctor that was unaware of which group the patient belong. Results: Both groups were similar before treatment, the group treated with enalapril did not present with enlargement of QTc, but the group treated with placebo developed a significant enlargement of QTc in every day of electrocardiographic evaluation measured in second (Average±SD) 5th day: enalapril 0,405±0,015 x placebo 0,437±0,030 (p=0,0019) , 10th day enalapril 0,408±0,019 x placebo 0,438±0,026 (p=0,0011), 15th day enalapril:0,407±0,017 x placebo 0,447±0,020(p<0,0001), 25th enalapril 0,404±0,019 x placebo 0,443±0,025 (p=0,002) e 35th: enalapril 0,395±0,028 x placebo 0,432±0,035(p=0,014). The relative risk of developing mild cardiotoxicity was lower the group received enalapril on 5th, 10th, 15th and e 25th day of evaluation (Relative risk(CI 95%)) 5th day: 0,53(0,33-0,86) (p=0,0063) , 10º day: 0,57(0,33-0,93)(p=0,0352), 15ºday 0,53(0,33-0,86) (p=0,0063), 25ºday 0,53(0,0063) (p=0,0063), but there were none difference on 35th day 0,80(0,62-1,03) (p=0,224). There were none difference in other variables in this study. Adverse effect were reported in 91,67% of patients and the frequency were similar in both groups. Conclusions:Enalapril has a cardioprotective effect during treatment of CL with meglumine antimoniate.